Teaching empathy and conflict resolution to people with dementia : a guide for person-centered practice - Camp, Cameron J.; Camp, Linda, 1952- (Jessica Kingsley Publishers, 2018)
This guide demonstrates how to employ empathy and respect when caring for older people with dementia. By addressing these virtues in the care model, the authors show how people with dementia can develop positive conflict resolution skills and the ability to self-initiate in matters concerning their own care for greater independence and wellbeing.